The Itsoseng settlement housing intervention in Johannesburg - Nyikavaranda, Pamela Chiratidzo (My University, 2018)
The purpose of this research was to assess beneficiaries’ perceptions regarding improvements in their safety and residential quality of life following a housing intervention programme in Itsoseng Informal Settlement. Initially, this study interrogated literature to comprehend assessments carried out in various housing interventions. Maslow Hierarchy of Needs, Quality of Life Theory and Max- Neef Human Needs Theory of Development were the theoretical frameworks used to understand how beneficiaries perceived the upgrading programme. Improvement in their residential quality of life is realised through the possibilities that are available to satisfy their crucial needs. For this reason, this research focused on assessing the beneficiaries’ perceptions on their safety and residential quality of life following the upgrade programme. Univariate analysis, bivariate analysis, paired sample t-test statistics and one-way analysis of variance (ANOVA) was utilised to analyse the perceptions of beneficiaries following a housing upgrade. The findings showed a good level of agreement between beneficiaries regarding their safety and residential quality of life, and there were no significant difference in the perceptions of male and female beneficiaries. Open-ended questions gave insight on the need to further improve beneficiaries’ satisfaction, particularly regarding services such as electricity, clinics, schools and safety walls. Pulling all these things together, the study highlighted the need to prioritise the preferences of beneficiaries, complemented by a comprehensive improvement on safety and residential quality of life to ensure user satisfaction. Insights from the findings further highlighted that holistic improvement in housing conditions, safety, basic services, building a good sense of belonging and tenure security is crucial and goes a long way towards enhancing improvement in the residential quality of life. This study facilitated the recommendations on improvement in the design of the houses in order to satisfy human needs rather than just focusing on the physical aspects of the house. This further allowed this study to emphasise that development is about people not objects, and that it is vital to steer the development process.
Thesis presented in partial fulfilment for the degree of Master of Management (in the field of Public Sector Monitoring and Evaluation) to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, March 2018
Keywords: Housing--South Africa--Johannesburg; Real property--Valuation